Histopathological Features of Vanishing Testes in 332 Boys: What Is Its Significance? A Retrospective Study From a Tertiary Hospital - Gao, Lei; Tang, Daxing; Gu, Weizhong (Frontiers in Pediatrics, 2022)
The purpose of this study is to analyze the histopathological features of resected testicular remnant specimens, ascertain the incidence of the presence of either germ cells (GCs) or seminiferous tubules (SNTs), and assess whether surgical excision of the remnant is necessary. A total of 332 boys with vanishing testis underwent surgical removal of unilateral testicular remnants, with age 7 to 164 months (median age 25 months). Among the total 332 cases, 212 (63.8%) were younger than 36 months and 143 (66.5%) were found to have hypertrophied contralateral testes larger than 1.6 cm in longitudinal diameter under sonography. SNTs were only present in 21 (6.3%) cases and GCs were present in 7 (2.1%) cases. Compared to the review studies, the very low incidence of SNTs and GCs in which implies extremely low chances of potential malignancy. We propose that surgical removal of vanishing testis remnants in an inguinal or scrotal position may not be necessary.